Students' extracurricular reading behavior and the development of vocabulary and reading comprehension - Pfost, Maximilian; Dörfler, Tobias; Artelt, Cordula (Learning and individual differences, 2013)
This study investigated the role of extracurricular reading behavior in the development of reading literacy. Whereas previous research has focused mostly on bivariate relations between one or several measures of these two variables, the present study analyzed the role of several reading activities together. Furthermore, it assessed distinct patterns of extracurricular reading behavior composed of traditional print media and new forms of reading on the Internet. Participants were 1226 secondary school students from the Bamberg BiKS longitudinal study. Results confirmed the importance of traditional book reading for the development of reading comprehension and vocabulary. In contrast, online activities such as e-mail or chatting related negatively to reading achievement. Furthermore, students could be classified to five distinct latent classes in terms of their extracurricular reading behavior. The role of reading traditional print media for students' literacy development as well as possible reasons why it cannot be compensated adequately by online reading activities are discussed critically.
Gesehen am 20.01.2022